Massage Efflurage VCO Terhadap Pencegahan Dekubitus pada Pasien Tirah Baring di RSUD Pandan Arang Boyolali - Dela Nuvita Sari; Fida' Husain; Panggah Widodo (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Background: Decubitus ulcers are damage/death of the skin to the tissue under the skin, if not treated immediately it will be one of the factors a person dies. The prevalence of decubitus in America is around 25%, in Europe it is 10.5% and in England it is from 6.7% to 42.7%, and in Indonesia as a whole it is 33%.The implementation of preventing decubitus pharmacologically, one of which is by rubbing massage on the back which is called massage efflurage. Purpose: to determine whether there is an effect of massage efflurage on decubitus prevention. Method: this type of research is descriptive with a case study. The application was carried out on 2 patients selected by purposive sampling method with inclusion and exclusion criteria. This efflurage massage is carried out for 4-5 minutes 2x/day for 3 days. The research instrument used SOP massage efflurage by doing massage by applying a little rubbing pressure, observation sheets and informed consent. Results: from the results of observations made for 3 days on 2 respondents Ny. S and Mr. M indicates that the braden scale increases from day 2 and 3, which means that there is a reduced risk of developing decubitus in 2 respondents. Conclusion: there is an effect of VCO efflurage massage to prevent pressure sores in patients in the ICU.